2020
DOI: 10.3329/bjo.v26i1.47953
|View full text |Cite
|
Sign up to set email alerts
|

A Clinical Study on Etiological Factors and Management of Epistaxis at a Tertiary Level Hospital

Abstract: Background: Epistaxis is a common otolaryngological emergency worldwide affecting up to 60% of the population in their lifetime. This study was conducted to describe the etiological profile and treatment outcome of epistaxis at Dhaka Medical College Hospital, a tertiary care hospital in BANGLADESH. Objective: The study is carried out with an objective to evaluate on etiological profile and management of epistaxis. Methods: This cross sectional study was conducted among the emergency and adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 10 publications
0
7
0
2
Order By: Relevance
“…In this series, the patients' mean age was 47 years old; in another research study, it is 35.06 and 40 years. 24,25 Most of the subjects in our research were in the 6th decade (21.57%), followed by the 5th (16.99%) and 4th (15.03%) decade. Whereas as per studies reported by Watkinson majority of patients were in the 2nd decade (21.15%), followed by the 6th (19.23%) and 3rd decade (17.31%).…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…In this series, the patients' mean age was 47 years old; in another research study, it is 35.06 and 40 years. 24,25 Most of the subjects in our research were in the 6th decade (21.57%), followed by the 5th (16.99%) and 4th (15.03%) decade. Whereas as per studies reported by Watkinson majority of patients were in the 2nd decade (21.15%), followed by the 6th (19.23%) and 3rd decade (17.31%).…”
Section: Discussionmentioning
confidence: 80%
“…A comparable outcome was also recorded in Nigeria, in Tanzenia and Bangladesh. 9,25,27 According to the study of Islam et al, by using the direct method, controlled bleeding was achievable in eleven (10.57%) subjects. Eighty-six (82.69%) subjects were treated with anterior nasal packing, postnasal packing was given in 3 (2.89%) subjects, and 3.85% of subjects were treated surgically as they presented with bleeding intranasal tumour.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mucosa over the septum in this area is especially thin, making this the most common site of epistaxis [1].Less commonly, vessels in the posterior or superior nasal cavity will bleed, leading to the so called " posterior epistaxis ". Anterior epistaxis is usually controlled by local pressure or anterior nasal packing while posterior epistaxis often requires posterior nasal packing or arterial ligation.Recent advances in endoscopy have facilitated nasal examination ; however, the effective management of this condition depends on awareness of the probable sources of epistaxis and a comprehensive understanding of the nasal structure [2]. Epistaxis can occur at any age but is mainly in elderly.Its incidence is difficult to asses but it is expected that approximately 60% of the population will be affected by epistaxis at somepoint in their lifetime, with 6% requiring medical attention.…”
Section: Introductionmentioning
confidence: 99%
“…In the Bangladeshi context, the most widely accepted definition of slums (also known as informal urban settlements) is "settlements with a minimum of 10 households or a small and untidy housing unit with a minimum of 25 members and predominantly very poor quality; very high population density and room crowding; very poor environmental services, especially water and sanitation; very low socio-economic status; and lack of security of tenure" [1,2]. According to the Census of Slum Areas and Floating Population 2014, 22,27,754 people live in different slums in Bangladesh with almost 48% living in Dhaka city (the capital of Bangladesh) [3] and of which 10% are children under five years old (U5y) [4].…”
Section: Introductionmentioning
confidence: 99%